Analisis efektivitas pengendalian risiko operasional pada bank umum syariah di Indonesia - Adzkiya, Hida Amalia (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the effectiveness of operational risk control in Islamic commercial banks in Indonesia, focusing on policy implementation, organizational structure, use of technology, and compliance with sharia principles. Operational risk is one of the main challenges in the banking industry, including in Islamic banks that must balance operational efficiency and Islamic values ​​such as honesty, fairness, and trustworthiness. This study uses a qualitative approach by examining secondary data and literature studies related to risk control practices implemented at Bank Syariah Indonesia (BSI). The results of the study indicate that the effectiveness of risk control is reflected in the decrease in the BOPO ratio and the decrease in the number of risk events, as well as the successful implementation of risk management systems such as RCSA, KRI, and LED. In addition, the involvement of special units such as SOR, RBC, and DCOR as well as regulatory support from OJK strengthen the risk mitigation process. However, challenges such as low risk awareness and dependence on technology remain a major concern. Thus, increasing the effectiveness of operational risk control needs to be supported by strengthening a risk-aware culture, visionary leadership, and the use of modern technology that remains in line with sharia principles.